The Effect of Size Reduction and Different Oil Ratio on Microemulsion of Trigonella Foenum-Graceum and Phyllanthus Embilica Oils and Their Antioxidant Properties - Mohd Yazid, Muhammad Saiful Asri; Mansur, Sity Aishah (Progress in Engineering Application and Technology, 2024)
Nanotechnology has shown promise in improving the penetration of active ingredients to deeper skin layers, enabling better absorption and efficacy. Creating smaller or nano-sized molecules involves various techniques and factors, depending on the desired size, properties of the material, and the intended application. This study aims to employ ultrasonication to generate nanoemulsions and investigates the effect of oil ratio in the nanoemulsification process of oil extracted from Trigonella foenum-graecum (fenugreek) and Phyllanthus emblica (Indian gooseberry or amla). Using fixed ultrasonication parameters, nanoemulsions of fenugreek seed and amla oils with three different formulations (1:1, 1:2, and 2:1) were prepared. The characterization of nanoemulsions in terms of particle size was determined by zeta particle analyser. - Furthermore, Fourier transform infrared spectroscopy (FTIR) was used to investigate the chemical composition of the nanoemulsion, which focused on the retention of bioactive compounds in fenugreek oil. The total phenolic content as well as radical-scavenging antioxidant activity were also evaluated. The results show that ultrasonication significantly affects the physicochemical properties of nano emulsions, leading to a reduction in droplet size (% of difference) and increased stability (Gul, O., et al, 2018) In addition, the antioxidant properties of the nano-emulsified These findings highlight the importance of considering oil ratios in nanoemulsion formulation and highlight the potential of ultrasonication as a promising strategy to improve the pharmacological and bioactive properties of natural emphasis oils, which are used in various industries.